2002
DOI: 10.1128/jcm.40.11.4161-4165.2002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Enzyme-Linked Immunosorbent Assay (ELISA) with Affinity-Purified Em18 and an ELISA with Recombinant Em18 for Differential Diagnosis of Alveolar Echinococcosis: Results of a Blind Test

Abstract: Alveolar echinococcosis (AE) is the most potentially lethal parasitic zoonosis of the nontropical areas in the northern hemisphere, where cystic echinococcosis (CE) is also endemic. Both AE and CE are highly endemic in China, and both serologic detection of echinococcosis, either AE or CE, and differentiation of AE from CE are crucial problems. Evaluation of Western blot analysis (WB) and enzyme-linked immunosorbent assay (ELISA) for the Em18 antigen, using affinity-purified and recombinant Em18, was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 13 publications
3
43
0
Order By: Relevance
“…This is not an incomprehensible result, because it is known that a few CE patient sera react to rEm18 even though rEm18 is highly specific antigen for AE (11,12,16,18). These results indicated that the ICT is a sensitive and specific method for the diagnosis of E. multilocularis infection.…”
Section: Alveolar Echinococcosis (Ae) Caused By the Larval Stage Ofmentioning
confidence: 67%
See 1 more Smart Citation
“…This is not an incomprehensible result, because it is known that a few CE patient sera react to rEm18 even though rEm18 is highly specific antigen for AE (11,12,16,18). These results indicated that the ICT is a sensitive and specific method for the diagnosis of E. multilocularis infection.…”
Section: Alveolar Echinococcosis (Ae) Caused By the Larval Stage Ofmentioning
confidence: 67%
“…Therefore, immunological tests have been considered important methods to confirm clinical findings, to give diagnostic help by providing information on the parasite in case of unclear images, or to survey in areas of endemicity where imaging techniques are not readily available (4,9,11). Previously, we have reported an enzyme-linked immunosorbent assay (ELISA) and an immunoblot analysis (IB) by using recombinant E. multilocularis 18-kDa antigen (Em18), the breakdown product of ezrin-radixin-moesin-like protein (2) that is also known as EM10 (8), EM II/3 (7), or EM4 (10) by the cysteine peptidase, and demonstrated that these two tests have a high potential for differentially diagnosing AE (1,12,16,18). However, these two methods are time-consuming and require special materials and equipments, which make them not suitable for clinical applications.…”
Section: Alveolar Echinococcosis (Ae) Caused By the Larval Stage Ofmentioning
confidence: 99%
“…These antigens have diagnostic sensitivities ranging between 81 and 100% and discriminate between AE and CE with a reliability ranging from 80 to C95% [15,26,27,[43][44][45][46]. The native and partially purified antigens tested in our study did not discriminate between AE and CE: they all recognised all AE and at least 81.3% of CE cases.…”
Section: Discussionmentioning
confidence: 88%
“…Antigen B (AgB) was prepared as described elsewhere [24,25], the Em2(G11) antigen was prepared as described by Deplazes et al [15], and the recombinant Em18 antigen was provided by the Institute of Parasitology in Bern, Switzerland [26,27].…”
Section: Defined Antigensmentioning
confidence: 99%
“…Serum samples were collected from the following groups of patients with AE and CE after appropriate ethical approval was obtained and informed consent was obtained from the patients: 30 serum samples from patients with CE in France (14) and 30 serum samples from patients with CE in China confirmed by surgery; 20 serum samples from patients with CE in Australia confirmed by serology with Ag5 with or without surgery (17,18), followed by WB and ELISA with AgB of E. granulosus hydatid cyst fluid at Asahikawa Medical College (AMC) (20) (Table 1); 45 serum samples from patients with AE diagnosed by surgery plus Em18 serology at Hokkaido University Hospital and AMC; and 19 serum samples from patients with AE in France diagnosed by surgery plus serology with a commercially available kit (14,16). The major target antigens were Em18, Em16, and AgB in a whole larval extract of E. multilocularis (10,12,14,16). These serum samples were obtained from patients who had been confirmed to have CE or AE and do not necessarily represent samples taken from patients prior to their commencement of treatment surgically and/or chemotherapeutically.…”
Section: Methodsmentioning
confidence: 99%